A Modified Version of the Timed Up and Go Test for Children Who Are Preschoolers. Issue 4 (2016) - Verbecque, Evi; Vereeck, Luc; Boudewyns, An; Van de Heyning, Paul; Hallemans, Ann
Abstract : Purpose: This study investigated factors predicting the Timed Up and Go (TUG) test in children who are preschoolers, using a modified protocol of the TUG. Method: This was a cross-sectional study of children 3 to 5 years old (n = 192). Regression analysis identified predictive factors for TUG performances. Differences in mean values (standard deviation) were calculated for each age group. Results: The results of 172 children were analyzed. Age and ethnicity were predictive of TUG performance ( R 2 = 0.280). Children who are preschoolers with Flemish ethnicity need less time to perform the TUG than their peers with another ethnicity ( P < .05), but this difference is not significant for the age groups. The TUG performance differs significantly among all age groups ( P < .05). Conclusions: A modified protocol for the TUG, which is sensitive to age-related changes in dynamic balance control, is proposed for children who are preschoolers. Abstract : This study investigated factors predicting Timed Up and Go using a modified protocol of the TUG to test in children who are preschoolers.